1983
DOI: 10.1002/ar.1092070409
|View full text |Cite
|
Sign up to set email alerts
|

The effects of beta adrenoceptor blockade with atenolol on myocardial cellular and subcellular hypertrophy in spontaneously hypertensive rats

Abstract: In this study we investigated the effects of chronic beta adrenoreceptor blockade with atenolol on cellular and subcellular hypertrophy in spontaneously hypertensive rats (SHR). Atenolol was injected subcutaneously (20 mg/kg) twice daily commencing in four-week-old rats. The treated animals (SHR-A) were compared to their nontreated controls and normotensive, Wistar-Kyoto (WKY) controls at the age of 16 weeks. A group of atenolol-treated WKY was also studied. Chronic drug treatment was effective in attenuating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
(41 reference statements)
0
2
1
Order By: Relevance
“…This report supports our present experimental results. However, Lauva and Tomanek reported that atenolol reduced LV weight in male SHRs at 4 weeks of age (29). The discrepancy between these results may be related to the experimental methods used (e.g., the age and sex of rats, or the different drugs used), however, our results indicate that the inhibition of RAS plays a more important role than the suppression of the β adrenergic nervous system in the reversal of myocyte remodeling.…”
Section: Discussioncontrasting
confidence: 73%
“…This report supports our present experimental results. However, Lauva and Tomanek reported that atenolol reduced LV weight in male SHRs at 4 weeks of age (29). The discrepancy between these results may be related to the experimental methods used (e.g., the age and sex of rats, or the different drugs used), however, our results indicate that the inhibition of RAS plays a more important role than the suppression of the β adrenergic nervous system in the reversal of myocyte remodeling.…”
Section: Discussioncontrasting
confidence: 73%
“…Pressure-overload-induced cardiac hypertrophy has been associated with increased serum epinephrine (Womble et al, 1978), the predominant adrenal catecholamine. Treatment of spontaneously hypertensive rats with a-methyldopa, a catecholamine depleting agent, or atenolol, a cardioselective P-adrenoceptor blocking agent, did modify cardiac hypertrophy (Sen et al, 1974;Tomanek et al, 1979;Lauva and Tomanek, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies employing adrenal demedullation (8), a-or P-adre-noceptor blockade ( 1 ), or chemical sympathectomy ( 17) have generally supported the view that adrenergic intervention has little or no effect on the hypertrophic response to pressure overload. Similarly, sympathectomy or P-adrenoceptor blockade does not prevent cardiac hypertrophy in spontaneously hypertensive rats (24)(25)(26), renal hypertensive rats (27), or rabbits subjected to hypoxia (28,29).…”
mentioning
confidence: 99%